A proposed resource room program for children with behavioral problems in San Jose District, Antique - Villavert, Rosalinda Petinglay 1946- (1977)
The research aimed to devise a plan to mobilize existing community and human resources towards educational ends, commonly shared by the regular and special teachers. The program would cater to the needs of children with behavioral problems in San Jose District, Antique. The proposed resource room program provides direct and indirect services to teachers and pupils.
Vita.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Children with mental disabilities -- Education -- Philippines -- San Jose (Antique); Special education -- Philippines -- San Jose (Antique); Problem children -- Behavior modification